A new fluorogenic probe for the selective detection of carbon monoxide in aqueous medium based on Pd(0) mediated reaction1. Issue 21 (14th March 2015) - Pal, Siddhartha; Mukherjee, Manjira; Sen, Buddhadeb; Mandal, Sushil Kumar; Lohar, Somenath; Chattopadhyay, Pabitra; Dhara, Koushik
<x xml:space="preserve">Abstract</x> A coumarin-based fluorogenic probe, PCO-1, detects carbon monoxide selectively in buffer at pH 8.0 through the intramolecular cyclization–elimination pathway based on Pd(0) mediated reaction.